2000
DOI: 10.1016/s0924-9338(00)94552-8
|View full text |Cite
|
Sign up to set email alerts
|

P01.145 Amyloid beta peptide 1–40 influences a recognition site of hemicholinium-3 sensitive choline carriers and their proteolytic degradation

Abstract: adequate psychosocial support, and better coordination between infectious-diseases and substance-use clinic teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…The exact mechanism through which GKB modulates β-amyloid-suppressed ACh remains unknown. However, it is of interest to note that β-amyloid peptides have been shown to reduce high affinity choline uptake (Kristofikova et al, 2001), whereas ginkgo extract (EGb 761) has been reported to increase choline uptake in the hippocampal synaptosomes (Kristofikova and Klaschka, 1997). Therefore, GKB could have a direct effect in reversing the inhibitory effect of β-amyloid peptides by altering central cholinergic activities.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism through which GKB modulates β-amyloid-suppressed ACh remains unknown. However, it is of interest to note that β-amyloid peptides have been shown to reduce high affinity choline uptake (Kristofikova et al, 2001), whereas ginkgo extract (EGb 761) has been reported to increase choline uptake in the hippocampal synaptosomes (Kristofikova and Klaschka, 1997). Therefore, GKB could have a direct effect in reversing the inhibitory effect of β-amyloid peptides by altering central cholinergic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Causes could be as follows: (i) Ab is produced constitutively by brain cells including neurons and is present at pM-nM concentrations in the CSF of normal individuals, (ii) Ab, as well as APP, mediates both neurotrophic and neurotoxic effects, and finally (iii) Ab is secreted from healthy neurons in response to the neuronal activity, subsequently downregulates excitatory synaptic transmission and via this negative feedback can maintain physiological homeostatic mechanism [e.g., 12,13]. The neuromodulation actions of Ab are not restricted only to cholinergic system but hypofunction of basal forebrain cholinergic neurons mediated by low physiological concentrations seems to be the best documented so far [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It is surprising that actions of Ab have not been evaluated yet on hippocampal synaptosomes isolated from immature postnatal rats via measurements of a high-affinity choline uptake (HACU) values. It is well known that physiological pM-nM concentrations of Ab inhibit HACU transport that is directly associated with a synthesis of acetylcholine as a key regulatory step in the mature brain tissue [14][15][16]. It seems that the inhibition could occur by a direct interaction of Ab with hemicholinium-3 (HC-3) sensitive choline carriers [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting floating particulate layer (synaptosomal fraction) was collected by decantation, washed with the homogenizing medium, and gently resuspended in the same medium. After the protein content of the preparations was determined (14), freshly prepared synaptosomes were immediately used in either assays of acetylcholine release (15) or assays of choline uptake (16).…”
Section: Acetylcholine (Ach) Which Is Synthesized From Choline (Ch)mentioning
confidence: 99%